Orthopedic physical assessment - Magee, David J. (Musculoskeletal rehabilitation series, 2014)
Newly updated, this full-color text offers a rich array offeatures to help you develop your musculoskeletal assessment skills. Orthopedic Physical Assessment, 6th Edition provides rationales for various aspects of assessment and covers every joint of the body, as well as specific topics including principles of assessment, gait, posture, the head and face, the amputee, primary care, and emergency sports assessment. Artwork and photos with detailed descriptions of assessments clearly demonstrate assessment methods, tests, and causes of pathology